2020
DOI: 10.3390/jcm9072264
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Clinical and Serological Features of COVID-19 in Urban Hemodialysis Patients

Abstract: Introduction: The inherent immunosuppression of uremia increases the susceptibility of hemodialysis patients to infection. There is still limited evidence on hemodialysis patients and COVID-19. The clinical and analytical spectrum and treatment responses and mortality are poorly characterized. Material and Methods: Clinical and analytical features, chest X-ray, polymerase chain reaction (PCR) and antibodies for SARS-CoV-2, treatment and outcomes were analyzed in 48 patients diagnosed with COVID-19 during March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
1
22
1
3
Order By: Relevance
“…Our global incidences are lower compared with the first published haemodialysed patient cohorts from Brescia, Italy (15%) [ 8 ] and Madrid, Spain (13%) [ 10 ], but higher compared with the cohort from Wuhan, China (2.5%) [ 9 ]. More recently, new cohorts from Italy [ 14 ] and Spain [ 15 ] report similar results, with higher incidences (26 and 24%, respectively) compared with the second published cohort from Wuhan, China (3.5%, despite a large screening of asymptomatic by chest CT) [ 16 ]. Canadian [ 17 ] and Turkish [ 18 ] cohorts reported incidences of 4.6 and 1.1%, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our global incidences are lower compared with the first published haemodialysed patient cohorts from Brescia, Italy (15%) [ 8 ] and Madrid, Spain (13%) [ 10 ], but higher compared with the cohort from Wuhan, China (2.5%) [ 9 ]. More recently, new cohorts from Italy [ 14 ] and Spain [ 15 ] report similar results, with higher incidences (26 and 24%, respectively) compared with the second published cohort from Wuhan, China (3.5%, despite a large screening of asymptomatic by chest CT) [ 16 ]. Canadian [ 17 ] and Turkish [ 18 ] cohorts reported incidences of 4.6 and 1.1%, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…The mortality rate in our study, while very much higher than that observed in the general population [ 4 ], is comparable to cohorts from Wuhan (31%) [ 9 ], Brescia (28%) [ 8 ] and Madrid (30%) [ 10 ]. The recently published cohorts reported a mortality of 43% in China [ 16 ], 25% in Italy [ 14 ] and 10% in Spain [ 15 ], and no deaths have been reported from Canada [ 17 ] and Turkish [ 18 ] cohorts. The small numbers of COVID-19 cases in these studies may explain this heterogeneity concerning mortality.…”
Section: Discussionmentioning
confidence: 99%
“…(2) 45 cross-sectional or cohort studies [18][19][20][21][22][23]25,26,29,31,32,35,37,[39][40][41][42][43][44]47,48,[51][52][53][54][55][56][58][59][60][61][62][63][64][67][68][69]71,[74][75][76][77][78][79][80] characterizing the antibody response (i.e., antibody types, levels, and duration) among adults with SARS-CoV-2 infection; and 317 studies validating the diagnostic performance of one or more immunoassays. 16,17,24,27,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Staines, 2020 59 Hypertension and body mass index were associated with seroconversion. Stock da Cunha, 2020 60 Among patients with end-stage renal disease on hemodialysis, 13% of patients had not developed antibodies at a mean of 13 days after having a positive PCR. Wang B, 2020 68 Among patients with multiple myeloma, 96% (22/23) Chen, Y.…”
Section: (Guangzhou China)mentioning
confidence: 99%
“…Estudios recientes están caracterizando la naturaleza de COVID-19 en los pacientes con ERC, diálisis o trasplante, identificando factores de riesgo para enfermedad grave y mortalidad, así como el patrón de temporal de la alteraciones clínicas y analíticas (21)(22)(23)(24)(25)(26). No obstante, no hay información sobre la respuesta ante la vacunación, que puede ser deficiente (27).…”
Section: Albertounclassified